The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1159/000167789
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Excretion of Pentose Phosphate Pathway-Associated Polyols in Early Postnatal Life

Abstract: Background: Two new inborn errors in the pentose phosphate pathway have been described: ribose-5-isomerase deficiency and transaldolase deficiency. These defects are characterized by accumulation of specific polyols in body fluids. Little is known about human polyol metabolism, but there are indications for a physiological role primarily during early development. Objectives: The objective of this study was to evaluate the urinary excretion of polyols in neonates with special interest on a possible impact of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…High polyol concentrations have been observed during fetal life, possibly playing a protective role against the low-oxygen environment [ 27 ] and regulating the fluid balance by acting as organic osmolytes [ 28 ]. High urinary excretion of pentose phosphate pathway-associated polyols was reported after birth in both preterm and term neonates [ 29 ], although other studies showed significantly decreased polyols (mannitol/sorbitol arabitol/xylitol and xylose) in the urine of neonates with necrotizing enterocolitis [ 10 ] and sepsis [ 30 ]. Interestingly, increased polyols including arabitol in the urine and other body fluids have been described in inborn errors of the pentose phosphate pathway involving deficiencies in ribose 5-phosphate isomerase or transaldolase [ 26 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…High polyol concentrations have been observed during fetal life, possibly playing a protective role against the low-oxygen environment [ 27 ] and regulating the fluid balance by acting as organic osmolytes [ 28 ]. High urinary excretion of pentose phosphate pathway-associated polyols was reported after birth in both preterm and term neonates [ 29 ], although other studies showed significantly decreased polyols (mannitol/sorbitol arabitol/xylitol and xylose) in the urine of neonates with necrotizing enterocolitis [ 10 ] and sepsis [ 30 ]. Interestingly, increased polyols including arabitol in the urine and other body fluids have been described in inborn errors of the pentose phosphate pathway involving deficiencies in ribose 5-phosphate isomerase or transaldolase [ 26 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to previously reported data, the normal value for galactose in whole blood was set at ≤ 240 μmol/l (Rommel et al 1968). Galactose-1-phosphate and galactitol in red blood cells (RBC) as well as galactose and galactitol in urine were measured by stable-isotope dilution analyses as recently described (Koy et al 2009;Schadewaldt et al 2003a, b). According to previously published data, the upper cut-off level for galactitol in RBC was set at 0.8± 0.2 μmol/l (Schadewaldt et al 2003a, b).…”
Section: Methodsmentioning
confidence: 99%
“…According to previously published data, the upper cut-off level for galactitol in RBC was set at 0.8± 0.2 μmol/l (Schadewaldt et al 2003a, b). Age-related reference values for galactitol in urine were determined by random sampling in healthy neonates and infants, and by postabsorptive sampling in healthy children, adolescents, and adults in a total of 225 samples (Koy et al 2009;Schadewaldt et al 2003a, b).…”
Section: Methodsmentioning
confidence: 99%